Preparation of phosphotungstic acid hybrid proton exchange membranes by constructing proton transport channels for direct methanol fuel cells. (16th January 2023) - Zhang, Yuanjing; Song, Yingxu; Chen, Dandan; Jin, Qifeng; Chen, Jinyao; Cao, Ya
Abstract: For direct methanol fuel cells (DMFCs), a unique hybrid proton exchange membrane (PEM) made of polyvinyl alcohol (PVA) and quaternized polyethyleneimine (QPEI) is presented. Employing QPEI as an anchoring agent is advantageous for enhancing the compatibility of the organic-inorganic interface when phosphotungstic acid (PWA) is used as the proton conductor on the assumption that the leakage of PWA is successfully reduced. Utilizing polymers as a substrate reduces the high solubility of PWA in water owing to hydrogen bonding and electrostatic interactions. Additionally, PWA performs the function of successive proton transport channels in the optimized PVA-QPEI-2 PEM, resulting in a maximum proton conductivity of 194.5 mS cm −1 and residual proton conductivity of more than 80% after 30 days of soaking in deionized water at 80 °C. Furthermore, the fuel cell assembled with PVA-QPEI-2 PEM delivers a peak power density of 147.2 mW cm −2 at 60 °C and 40% relative humidity. Noteworthily, this organic-inorganic hybrid PEM containing PWA as a proton carrier is fabricated by a remarkably simple method, which has a methanol permeability that is an order of magnitude less than the Nafion® used in commercial applications, demonstrating its competitive potential for application in DMFCs. Graphical abstract: Image 1 Highlights: Preparing PVA cross-linked with QPEI proton exchange membranes using PWA as the proton conductor. The methanol permeability of the hybrid proton exchange membrane decreases. Immobilized PWA in membranes facilitates the construction of proton transport channels. Employing QPEI conquers the poor compatibility between the organic and inorganic interface.